A Switching Adaptive Current Controller for BLDCM Drives - Adiguzel, Fatih; Turker, Turker (IEEE, 2017)
A switching adaptive controller is proposed to control the phase currents in brushless DC motor (BLDCM) drives. After deriving the error dynamics, the conduction and commutation periods of the drive is taken into account separately, and two different controllers are designed for each operation region of the current loop of BLDCM drives. All the system constants in the dynamical model of the drive are considered uncertain, and adaptation rules are derived for these unknown parameters. The stability of the closed-loop system is shown by a common Lyapunov function, and the convergence of the current error to zero is proved as well. Various numerical simulations are performed for different working conditions to test the viability of the designed controller.
Keywords: Switching controller; brushless DC motor drives; adaptive control; COMMUTATION TORQUE RIPPLE; NONLINEAR-SYSTEMS; LINEAR-SYSTEMS; STABILITY; FEEDBACK; STABILIZATION; DESIGN; Automation & Control Systems; Robotics